2020
DOI: 10.1111/hel.12700
|View full text |Cite
|
Sign up to set email alerts
|

PCR analysis and specific immunohistochemistry revealing a high prevalence of non‐Helicobacter pylori Helicobacters in Helicobacter pylori‐negative gastric disease patients in Japan: High susceptibility to an Hp eradication regimen

Abstract: Background The clinical significance of non‐Helicobacter pylori Helicobacter (NHPH) is still unknown. There are many reports of NHPH‐infected patients suffering from gastric diseases. Here, we investigated the polymerase chain reaction (PCR) positivity of NHPH infection in gastric disease patients who were negative for H. pylori (Hp) by the rapid urease test and by pathological observation. Materials and methods We collected the 296 endoscopically obtained gastric mucosal samples of Hp‐negative gastric disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 24 publications
(29 reference statements)
5
48
0
Order By: Relevance
“…Effects of antibiotics were particularly observed in patients with localized disease [34,35]. In addition, Helicobacter species other than H. pylori have been suspected to explain the antibiotic treatment responses [36,37]. In the present study, nine H. pylori negative patients were treated with antibiotics (stage I, n = 6; stage II, n = 2; stage IV, n = 1).…”
Section: Discussionmentioning
confidence: 79%
“…Effects of antibiotics were particularly observed in patients with localized disease [34,35]. In addition, Helicobacter species other than H. pylori have been suspected to explain the antibiotic treatment responses [36,37]. In the present study, nine H. pylori negative patients were treated with antibiotics (stage I, n = 6; stage II, n = 2; stage IV, n = 1).…”
Section: Discussionmentioning
confidence: 79%
“…A combination therapy with a proton pump inhibitor (PPI), amoxicillin, and clarithromycin or metronidazole has been reported to be effective to eradicate NHPH. 7,[14][15][16] We previously reported two cases of chronic NHPH infection in which the patients were cured with a combination therapy of PPI, amoxicillin, and clarithromycin for one week at our institution 8 In addition, we reported in the same report that, in 4 of 6 (66.7%) patients who had had persistent infection of NHPH, NHPH was successfully eradicated with long-term (6 months) administration of PPI alone. 8 On the other hand, Iwamoto et al reported that AGML caused by H. pylori was cured spontaneously without eradication therapy in 21 of 26 cases.…”
Section: Discussionmentioning
confidence: 79%
“…At present, there is no clear consensus on the eradication of persistently infected NHPH that causes chronic gastritis. A combination therapy with a proton pump inhibitor (PPI), amoxicillin, and clarithromycin or metronidazole has been reported to be effective to eradicate NHPH 7,14‐16 . We previously reported two cases of chronic NHPH infection in which the patients were cured with a combination therapy of PPI, amoxicillin, and clarithromycin for one week at our institution 8 In addition, we reported in the same report that, in 4 of 6 (66.7%) patients who had had persistent infection of NHPH, NHPH was successfully eradicated with long‐term (6 months) administration of PPI alone 8…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations